1, 8-Cineole ameliorates right ventricle dysfunction associated with pulmonary arterial hypertension by restoring connexin43 and mitochondrial homeostasis. (June 2022) - Alves-Silva, Jorge M.; Zuzarte, Mónica; Marques, Carla; Viana, Sofia; Preguiça, Inês; Baptista, Rui; Ferreira, Cátia; Cavaleiro, Carlos; Domingues, Neuza; Sardão, Vilma A.; Oliveira, Paulo J.; Reis, Flávio; et al.
Abstract: For the first time, the present study unravels a cardiospecific therapeutic approach for Pulmonary Arterial Hypertension (PAH), a disease with a very poor prognosis and high mortality rates due to right ventricle (RV) dysfunction. We first established a new in vitro model of high-pressure-induced hypertrophy that closely resembles heart defects associated with PAH and validated our in vitro findings on a preclinical in vivo model of monocrotaline (MCT)-induced PAH. Our results showed the in vitro antihypertrophic effect of 1, 8-cineole, a monoterpene widely found in several essential oils. Also, a decrease in RV hypertrophy and fibrosis, and an improvement in heart function in vivo was observed, when 1, 8-cineole was applied topically. Furthermore, 1, 8-cineole restored gap junction protein connexin43 distribution at the intercalated disks and mitochondrial functionality, suggesting it may act by preserving cardiac cell-to-cell communication and bioenergetics. Overall, our results point out a promising therapeutic compound that can be easily applied topically, thus paving the way for the development of effective cardiac-specific therapies to greatly improve PAH outcomes. Graphical Abstract: ga1 Highlights: High pressure induces cell hypertrophy, which is reverted by 1, 8-cineole. 1, 8-Cineole showed a cardiospecific accumulation in diseased animals. 1, 8-Cineole decreases right ventricle hypertrophy. 1, 8-Cineole restores connexin43 distribution and levels in an animal model of PAH. 1, 8-Cineole improves mitochondrial functionality both in vitro and in vivo .